2017
DOI: 10.1007/s11547-017-0775-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of a contouring guide in three different head set-ups for hippocampal sparing radiotherapy: a practical approach

Abstract: Our guide can represent a useful tool for hippocampal delineation in clinical practice and for different anatomic variations due to different head positions. Certainly, it should be validated in practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Finally, Di Biase et al showed that the head position on the treatment table can affect hippocampal appearance. To solve the problem, they developed a practical guide for hippocampus delineation based on three different head position setups [42].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Di Biase et al showed that the head position on the treatment table can affect hippocampal appearance. To solve the problem, they developed a practical guide for hippocampus delineation based on three different head position setups [42].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, gadolinium, an MRI contrast medium, provides better localization as before of the choroid plexus, one of the anatomic areas of the hippocampus. Therefore, use of both sequences, with and without MRI T1 contrast, may contribute to a more precise delineation of the hippocampus [30,35,39]. To date, the T1 MRI sequence without contrast enhancement is the most frequently used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%